2021
DOI: 10.1371/journal.pone.0253487
|View full text |Cite
|
Sign up to set email alerts
|

The Fc-mediated effector functions of a potent SARS-CoV-2 neutralizing antibody, SC31, isolated from an early convalescent COVID-19 patient, are essential for the optimal therapeutic efficacy of the antibody

Abstract: Although SARS-CoV-2-neutralizing antibodies are promising therapeutics against COVID-19, little is known about their mechanism(s) of action or effective dosing windows. We report the generation and development of SC31, a potent SARS-CoV-2 neutralizing antibody, isolated from a convalescent patient. Antibody-mediated neutralization occurs via an epitope within the receptor-binding domain of the SARS-CoV-2 Spike protein. SC31 exhibited potent anti-SARS-CoV-2 activities in multiple animal models. In SARS-CoV-2 in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 59 publications
6
84
0
Order By: Relevance
“…To this end, a subset of monoclonal antibodies isolated from SARS-CoV patients that were able to cross-react with, but not neutralize SARS-CoV-2 were able to confer protection in a mouse model 42 . Indeed, both passive transfer experiments of monoclonal antibodies [43][44][45][46][47] and evaluation of polyclonal antibodies raised in the context of vaccination or infection [48][49][50] have shown that effector mechanisms contribute to antiviral activity in vivo. This evidence extends beyond correlative observations 45,48 to include mechanistic 1 evidence of in vivo contributions via Fc sequence engineering to knockout or enhance these activities 44,46 , as well as on the basis of depletion of effector cells 46 .…”
Section: Discussionmentioning
confidence: 99%
“…To this end, a subset of monoclonal antibodies isolated from SARS-CoV patients that were able to cross-react with, but not neutralize SARS-CoV-2 were able to confer protection in a mouse model 42 . Indeed, both passive transfer experiments of monoclonal antibodies [43][44][45][46][47] and evaluation of polyclonal antibodies raised in the context of vaccination or infection [48][49][50] have shown that effector mechanisms contribute to antiviral activity in vivo. This evidence extends beyond correlative observations 45,48 to include mechanistic 1 evidence of in vivo contributions via Fc sequence engineering to knockout or enhance these activities 44,46 , as well as on the basis of depletion of effector cells 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the interest in understanding the role of Fc in the in-vivo neutralization of SARS-CoV-2, only limited studies have addressed this point so far. Two studies have performed a side-by-side comparison of the in-vivo activity of a mutated Fc (LALA or LALA-PG) versus a fully active antibody [ 27 , 28 ]. Both studies have found that treatment outcome, when given post-exposure (2–24 h post-infection), was markedly affected if Fc-mediated activity was abrogated.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that when given prophylactically, the protective activity of the mutated antibodies was minorly affected [ 25 , 26 , 27 ]. However, delaying the treatment, even for a short period (2–24 h post infection) markedly reduced viral clearance and the therapeutic effect conferred by these Fc-null antibodies [ 26 , 27 , 28 ]. The results of these studies may imply that once virus replication has begun, direct antibody neutralization is insufficient and other mechanisms that are based on Fc-activation are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Mutated in both the Alpha and the Beta variants, residue N501 is localized at the binding interface with ACE2 ( 34 , 65 ), and many reports have suggested that the N501Y substitution increases the affinity of the RBD for ACE2 ( 23 , 48 , 66 70 ; see reference 71 for a discrepant prediction), potentially explaining the elevated infectivity of the Alpha variant. In a study in which the effects of all possible RBD amino acid substitutions were examined using a yeast surface display platform, Starr et al identified N501Y as one of the substitutions causing the highest gain in ACE2-binding affinity ( 23 ).…”
Section: Discussionmentioning
confidence: 99%